PENGUJIAN TEGANGAN TEMBUS MINYAK TRAFO PADA BAY TRAFO 1 DI GI 150 kV TANJUNG - Maharani, Citra Putri; Nrartha, I Made Ari; Nugroho, Septian Ilham; Hasibuan, Arnawan (Universitas Lampung, 2024)
The transformer is the main component in a substation (GI). Transformer failure causes continuity of electricity service to be disrupted. One preventive maintenance to avoid transformer failure is testing the breakdown voltage of the transformer oil. Breakdown voltage testing is carried out routinely once a year. This research tested the transformer oil breakdown voltage in transformer bay 1 at the GI of Tanjung 150 kV. Testing was carried out using procedures and methods that refer to the 1995 IEC 60156-02 standard with mushroom electrodes and an electrode distance of 2.5 mm. Oil samples from the main tank and from the Tap Changer. The average breakdown voltage test results were 59.4 and 36 kV/2.5 mm for oil in the main tank and in the Tap Changer. The test results according to the breakdown voltage criteria for transformer oil referring to the 2013 IEC 60422 standard are good or still suitable for use.